Comparative study between efficacy of topical tofacitinib 2% ointment versus topical clobetasol propionate 0.05% ointment in hand eczema at a tertiary hospital in central India [version 1; peer review: 2 approved] - Dr Adarshlata Singh; Drishti Bhatt (F1000Research)
Background Hand eczema is a prevalent dermatological condition that significantly impacts the quality of life of affected individuals. Topical corticosteroids, such as Clobetasol Propionate, are commonly employed for management, but concerns regarding long-term use and potential side effects necessitate exploration of alternative treatments. This study protocol outlines a randomized controlled trial comparing the efficacy of topical Tofacitinib 2% ointment with Clobetasol Propionate 0.05% ointment in managing hand eczema. Methods The study will be a single-blinded, parallel-group, randomized controlled trial conducted at the Dermatology outpatient department of Acharya Vinoba Bhave Rural Hospital Sawangi Meghe, Wardha, from March 2023 to September 2025. Eligible participants diagnosed with hand eczema will be randomized into two groups: Group 1 will receive Clobetasol Propionate 0.05% ointment, and Group 2 will receive Tofacitinib 2% ointment. The primary outcome measure is the change from baseline in the Hand Eczema Severity Index (HECSI) score, assessed at two weeks and four weeks. Statistical analysis will utilize appropriate parametric and non-parametric tests, with a p-value <0.05 considered significant. Expected Outcome The study is anticipated to provide insights into the comparative efficacy and safety of Tofacitinib and Clobetasol Propionate in managing hand eczema. A favorable outcome for Tofacitinib could suggest its potential as an alternative or adjunctive therapy, offering a more targeted approach with fewer side effects. The findings may contribute to optimized treatment strategies for hand eczema, improving patient outcomes and guiding future research in dermatological therapeutics.